Inner working models in intimate relationships – adult attachment and time perspective - Huić, Aleksandra; Kamenov, Željka (2010)
Depending on whether we have positive or negative inner working models of self and others, our behavior, emotions and judgment in intimate relationships will be different. Recently, another inner working model - time perspective (TP) - re-emerged as a construct which is claimed to have an important influence on human behavior. TP is conceptualized as a process by which we organize our experiences in temporal categories (past, present, future) to give order, meaning and structure to different events in our lives. Individual differences in these frames are thought to lead to differences in judgement, emotions and action. This study tested the relationship between these two kinds of inner working models. We hypothesized that securely attached individuals will also be past-positive, present-hedonistic and future oriented. These TP dimensions are associated with good adjustment and absence of pathology. Other attachment styles should be related to past-negative and present-fatalistic orientations. We were also interested in whether the hypotheses made for these individual differences will be confirmed on the behavioral level. 300 students and young adults, that are currently in romantic relationships, participated in the study. Modified version of Brennan's Experience in Close Relationships Inventory (Kamenov and Jelic, 2003) and Zimbardo Time Perspective Inventory (Zimbardo and Boyd, 1999) were administered. We also asked participants about specific habits and behaviors they exhibit in their current relationship. Relations between attachment styles and TP dimensions (operationalized both with inventories and specific behaviors) are discussed.
Projekt MZOS
ENG